Benefits of Individual Counseling Services and Group Counseling Services in Fostering the Morals of Students of MTSN 1 Deli Serdang - Mahfidz, Irgan Khairul; Daulay, Nurussakinah; Rusman, Abdul Aziz (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Individual counseling services are the heart of all counseling services so that this service becomes the main reference in solving problems that occur in students at MTs Negeri 1 Deli Serdang school. This research fulfills the characteristics of qualitative research. This research is field research using a phenomenological approach. Data collection techniques are carried out by: 1) Observation; 2) Interviews and 3) Documentation Studies. Analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. Data validity tests in qualitative research include, data credibility test, transferability test, dependability test, and confirmablity test. the results show a good direction with the counseling process undertaken. Evidenced by the change in student morals from a bad person to a better person. The benefits provided in individual counseling services and group counseling services make communication between counseling teachers and students active with individual counseling services making the approach method a step in inviting students to think about the problems they are facing and dare to reveal the problems they are facing. The success of individual counseling services and group counseling services can be seen from the changing behavior of students, from bad to good personalities.